A statistical study of heterogeneous nucleation of ice by molecular dynamics - Bermúdez Di Lorenzo, Aleida Josefina (2015)
Fil: Bermúdez Di Lorenzo, Aleida Josefina. Universidad Nacional de Córdoba. Facultad de Matemática, Astronomía y Física; Argentina.